A transferência de trabalho no Ensino Remoto Emergencial: experiências subjetivas no Estágio Supervisionado de Língua Inglesa - Lígia Cristina Domingos Araújo (2023)
During the social distancing period imposed by the COVID-19 pandemic, new ways of learning and teaching, mediated by technology, became necessary with the implementation of Emergency Remote Teaching (ERT). This new teaching situation imposed a different way of relating to the body, one's own and the other's, in the virtual educational landscape. The effects of a corporeality that is distinct from what we were used to could be perceived in teaching and learning, because the body supports the transference of work — a bond that, according to Freudian-Lacanian psychoanalysis, is established between teachers and students and enables the transmission and production of knowledge. In the field of Applied Linguistics dedicated to the study of foreign language teacher education, with an emphasis on the Supervised Practicum (SP), we questioned whether, in the ERT, it would be possible to offer a remote practice to student teachers of English enrolled in the subject Supervised Practicum II of an English Teaching Major. As the practice proved to be possible, we further questioned what could be observed about the establishment of bonds between the participants that would translate into a transference of work. This implies the construction of singular knowledge about teaching and teacher education, as well as the subjective repositioning in relation with knowledge. Thus, this work investigates, from the perspective of Psychoanalysis, the incidence of transference of work and the elements that support it in the remote SP II situation, based on the listening of the subjects, which occurred through my observation of synchronous classes, my listening to the reports of the participants' experience, and my reading of the students' internship report. The formation of this discursive corpus allowed us to discuss the ways in which the bond between subjects was constituted and the effects that the partnerships had on their work. Two moments were observed during the transmission of knowledge: one in the virtual classroom, during the synchronous meetings, in which the transference of work between the SP Professor, Roberta, and her students prevailed; and another, during the practice, in which the bond between the student teachers, Taís and Camila and the practicum supervisor teacher, Laura, stood out. In both situations, we could see that the transference of work, just like it is sustained outside, was sustained in the virtual environment oriented by each subject's modes of drive satisfaction. However, in ERT, the forms of the object a, voice and gaze, that Lacan adds to Psychoanalysis, gain primacy. These objects projected in the virtual environment make the subject present, giving them a place in the signifying chain, which will give consistency to the symbolic, pulsional body, allowing the subjects to address themselves to others and establish a bond. We perceived, therefore, that the ERT does not modify one’s singularity in the search for the bond, but conditions its establishment to the circulation of these two objects. We also observed that, in this experience, the participants demonstrated that they had developed new knowledge about teacher education and the practicum, repositioning themselves in the face of constituted knowledge and producing subjective displacements related to their own desire.